The divergent logics of industrial change: a comparison of export-cheese processors in Nicaragua. (6th March 2019) - Fuentes, Alberto
Abstract: According to the industrial policy literature, market failures hamper industrialization processes among private sector firms. Its proposed state-centered solution builds on a conception of these firms as solely profit-maximizing and largely unable to independently solve collection action dilemmas. This article offers a more nuanced portrayal of the private sector's behavior. It draws upon a broad comparative institutional literature on embedded capitalism and an empirical study of the unexpected industrial transformation of cheese processors in rural Nicaragua to claim that nonmarket logics, such as the familial or community logics, may similarly impinge upon firm action. These logics endow firms with contrasting understandings of group boundaries, on the one hand, and organizational priorities and associated governance mechanisms, on the other—two factors that, together, produce divergent, and often effective, responses to collective action dilemmas. The article concludes with a review of the argument's implications for industrial policy.